MiRNA-based therapeutic potential in multiple sclerosis - Zabalza, Ana; Pappolla, Agustin; Comabella, Manuel; Montalban, Xavier; Malhotra, Sunny (Frontiers in Immunology, 2024)
This review will briefly introduce microRNAs (miRNAs) and dissect their contribution to multiple sclerosis (MS) and its clinical outcomes. For this purpose, we provide a concise overview of the present knowledge of MS pathophysiology, biomarkers and treatment options, delving into the role of selectively expressed miRNAs in clinical forms of this disease, as measured in several biofluids such as serum, plasma or cerebrospinal fluid (CSF). Additionally, up-to-date information on current strategies applied to miRNA-based therapeutics will be provided, including miRNA restoration therapy (lentivirus expressing a specific type of miRNA and miRNA mimic) and miRNA inhibition therapy such as antisense oligonucleotides, small molecules inhibitors, locked nucleic acids (LNAs), anti-miRNAs, and antagomirs. Finally, it will highlight future directions and potential limitations associated with their application in MS therapy, emphasizing the need for improved delivery methods and validation of therapeutic efficacy.